2000
DOI: 10.1002/(sici)1097-4695(20000215)42:3<287::aid-neu1>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Critical and optimal Ig domains for promotion of neurite outgrowth by L1/Ng-CAM

Abstract: Mammalian L1 and avian Ng-CAM are homologous neural cell adhesion molecules (CAMs) that promote neurite outgrowth and cell adhesion in most neurons. Previous attempts to map these activities to discrete regions in the CAMs have suggested the involvement of a variety of different domains. However, these studies mainly used bacterially expressed proteins that were much less active on a molar basis than the native molecules. To define regions that are critical for maximal neurite outgrowth, we constructed and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 0 publications
2
52
0
Order By: Relevance
“…The deduced full sequence of Losac indicates that the mature protein is made up of 395 amino acids resulting in a 43.4-kDa protein with a theoretical pI of 7.64 (JUFO program; available on the World Wide Web). Sequence Comparisons-Deduced amino acid sequence revealed variable percentages of identity with cell adhesion molecule members of the immunoglobulin superfamily: 26% identity with L1-NCAM (human neural cell adhesion molecule L1), which is involved in development of the nervous system and neurite outgrowth in humans (35); 34% identity with the four first domains of Neuroglian from Drosofila melanogaster (36), an ortholog of L1-NCAM; and between 47 and 76% identity with several members of the hemolin family (31). With the latter, rLosac shares the same multidomain structure (D1-D4, bars above sequences) and conserved motifs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deduced full sequence of Losac indicates that the mature protein is made up of 395 amino acids resulting in a 43.4-kDa protein with a theoretical pI of 7.64 (JUFO program; available on the World Wide Web). Sequence Comparisons-Deduced amino acid sequence revealed variable percentages of identity with cell adhesion molecule members of the immunoglobulin superfamily: 26% identity with L1-NCAM (human neural cell adhesion molecule L1), which is involved in development of the nervous system and neurite outgrowth in humans (35); 34% identity with the four first domains of Neuroglian from Drosofila melanogaster (36), an ortholog of L1-NCAM; and between 47 and 76% identity with several members of the hemolin family (31). With the latter, rLosac shares the same multidomain structure (D1-D4, bars above sequences) and conserved motifs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the sequence revealed that Losac shares different degrees of similarity with cell adhesion molecule members of the immunoglobulin superfamily involved in the development of the nervous system and critical for neurite outgrowth: hemolin from lepidopters (47-76%) (31,37), neuroglian (34%) from D. melanogaster (36), and L1-NCAM (26%) from humans (35).…”
Section: Discussionmentioning
confidence: 99%
“…The mouse CHL1-Fc and the mouse L1-Fc fusion proteins were produced and purified as described by Chen et al (1999) and Haspel et al (2000). They contain the extracellular domain of the mouse protein (CHL1 or L1) and the Fc region of the human IgG.…”
Section: Methodsmentioning
confidence: 99%
“…Details on the production and characterisation of the monoclonal CEACAM1 antibody 4D1/C2 (in house preparation by Christoph Wagener (CW)) and the polyclonal L1 antibody (L1-S; in house preparation by Meliha Schachner (MS)) have been published previously (Haspel et al, 2000).…”
Section: Immuno-histochemistrymentioning
confidence: 99%